Perancangan Buku Ilustrasi Perjalanan Mahapatih Gajah Mada - Soedarso, Nick (Humaniora, 2014)
Majapahit Kingdom was one of the great Hindu-Buddhist kingdom in Indonesian archipelago which brought great influence to the Southeast Asia civilization between the 13th-16th century. One of the most important figures of Majapahit kingdom was Gajah Mada, a famous name that exceeds even the King himself. Nowadays, history considered as an unattracting subject and it slowly becomes disappeared, which lead us to the lost of cultural values and knowledge. One way to keep the history interesting is to present the story in well presented illustration. The object of this thesis is the character of Gajah Mada and the story that developed around him. This thesis will try to depict the figure of Gajah Mada and illustrate the important moments of his life based on stories from legend and different historical sources and at the end, create a new interpretation of Gajah Mada. The design result of this illustrated book not oly pursue the function and aesthetic, but also as an act of cultural conservation in a creative way, which at the end enrich the story of Gajah Mada.